Chemical Signals are Involved in the Detection and Preference of Food Sources in Blattella Germanica - Xoana Magalí Santa Cruz; Valeria Sfara (Ital Publication, 2018)
The German cockroach (Blattella germanica) is a cosmopolitan omnivorous species which can take nutrients from a wide variety of sources. Its condition of pest generated interest in the study of its biology, and while there are many works regarding its feeding behavior, few approaches have been made to the relevance of the chemosensory system during foraging. Objective: In this work we studied the role of chemical stimuli in the detection and preference of food sources in B. germanica using behavioral observations. Methods: Adult males were placed in a circular experimental arena where different diet types were presented individually. Parameters associated to the detection of odors (latency to the food source, number of visits to the source) were measured in an experimental time of 15 minutes. We also measured the total amount ingested determining the weight gain of each individual, as an indicator of taste evaluation of food. Findings: Insects showed a lower latency when the source emitted a larger amount of volatile compounds, so peanut butter was detected faster compared with the other diets studied. Regarding ingestion, insects spent significantly more time on the peanut butter, indicating the presence of phagostimulants such as sugars or lipids. When sugar solutions were used as food sources, the number of visits, the time spent on the source and the amount consumed was higher when increasing sugar concentration. Insects also showed preference for the solution of higher concentration, when two sugar solutions were presented simultaneously. Latency increased and the amount of sugar ingested decreased when insects´ mouthparts were chemically blocked with N-Ethylmaleimide, a general inhibitor of chemoreception. Novelty/Improvement: These results describe how cockroaches use odors to locate food sources and chemoreceptors in their mouthparts to identify diets of higher energetic value, from information regarding the concentration and quality of the food source. Understanding the feeding behavior of cockroaches allows the design of more attractive and palatable toxic gel baits enhancing their efficacy for cockroach control.